Efforts to Overcome Career Confusion for High School Students by Increasing Career Involvement through CIP Individual Career Counseling - Hasna Hafizhah Salma; Eva Septiana (Department of Guidance and Counseling, FIP, Undiksha, 2022)
School counselors can help high school students who have career problems with career guidance or counseling. So far, previous research has mostly proven the effectiveness of career group counseling. Meanwhile, individual counseling is rarely seen for its effectiveness, even though it is possible to do it by considering unique personal characteristics. The purpose of this research is to look at the effectiveness of individual career counseling with the CIP approach to increasing career involvement to overcome the problem of career confusion for high school students. This research is an experimental research with a single subject. Data collection was carried out using career engagement questionnaires, interviews, and observations during the counseling process. Data analysis uses visual techniques. The results show that individual counseling can solve the problem of career indecision by increasing career engagement. The implications of this research can be applied to school counselors at the high school level.